Strain belonging to an emerging, virulent sublineage of ST131 Escherichia coli isolated in fresh spinach, suggesting that ST131 may be transmissible through agricultural products - Balbuena-Alonso, Maria G.; Camps, Manel; Cortés-Cortés, Gerardo; Carreón-León, Eder A.; Lozano-Zarain, Patricia; Rocha-Gracia, Rosa del Carmen (Frontiers in Cellular and Infection Microbiology, 2023)
Abstract Food contamination with pathogenic Escherichia coli can cause severe disease. Here, we report the isolation of a multidrug resistant strain (A23EC) from fresh spinach. A23EC belongs to subclade C2 of ST131, a virulent clone of Extraintestinal Pathogenic E. coli (ExPEC). Most A23EC virulence factors are concentrated in three pathogenicity islands. These include PapGII, a fimbrial tip adhesin linked to increased virulence, and CsgA and CsgB, two adhesins known to facilitate spinach leaf colonization. A23EC also bears TnMB1860, a chromosomally-integrated transposon with the demonstrated potential to facilitate the evolution of carbapenem resistance among non-carbapenemase-producing enterobacterales. This transposon consists of two IS26-bound modular translocatable units (TUs). The first TU carries aac(6')-lb-cr, blaOXA-1, ΔcatB3, aac(3)-lle, and tmrB, and the second one harbors blaCXT-M-15. A23EC also bears a self-transmissible plasmid that can mediate conjugation at 20 °C and that has a mosaic IncF [F(31,36):A(4,20):B1] and Col156 origin of replication. Comparing A23EC to 86 additional complete ST131 sequences, A23EC forms a monophyletic cluster with 17 other strains that share the following four genomic traits: (1) virotype E (papGII+); (2) presence of a PAI II536-like pathogenicity island with an additional cnf1 gene; (3) presence of chromosomal TnMB1860; and (4) frequent presence of an F(31,36):A(4,20):B1 plasmid. Sequences belonging to this cluster (which we named “C2b sublineage”) are highly enriched in septicemia samples and their associated genetic markers align with recent reports of an emerging, virulent sublineage of the C2 subclade, suggesting significant pathogenic potential. This is the first report of a ST131 strain belonging to subclade C2 contaminating green leafy vegetables. The detection of this uropathogenic clone in fresh food is alarming. This work suggests that ST131 continues to evolve, gaining selective advantages and new routes of transmission. This highlights the pressing need for rigorous epidemiological surveillance of ExPEC in vegetables with One Health perspective.